The Influence Of Service Quality Perseption Toward Inpatient Satisfaction At Mayjen H.A Thalib Hospital Kerinci 2016 - Listiawaty, Renny; Chandra, Eko (Journal of Global Research in Public Health, 2017)
In the global era, that becomes indicators of succcess of health service is a inpatient satisfaction. Patient will fell satisfied if they gain the health service more than their hope. There are five indicators of inpatient satisfaction are reliability, tangibles, responsiveness, assurance, emphaty. This research was the quantitative reserch with design cross sectional that has towards to know the influence of service quality perseption with inpatient satisfaction at Mayjen H.A Thalib Hospital Kerinci. Sample technique was propotional sampling, the samples were 95 respondens. Data were tested by chi-square test.The result was the patient felt satisfied with the servis health that given from Mayjen H.A Thalib Hospital Kerinci, and there were influence between perseption of service quality dimensions of reliability, responsiveness, assurance andemphaty toward inpatient satisfaction with the p-value 0.000, in addition there was no influence between perseption of service quality dimension of tangible with the p-value 0.647. Researcher hope that the hospital can set the schedule to medicinal treatment, with the result that the patient will not wait too long.